ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PENGELUARAN PEMERINTAH, TENAGA KERJA, PEKERJA BERPENDIDIKAN SMA KE ATAS, DAN INVESTASI TERHADAP KETIMPANGAN PENDAPATAN DI PROVINSI BALI TAHUN 2016-2020 - Trisa Novia (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
The problem of economic growth that often occurs in the regions is income inequality. Income inequality is a condition when the income received by a society is not evenly distributed. There is a gap between the high-income group and the low-income group. Inequality in the distribution of income will lead to disparities between regions. This study aims to identify the factors that influence income inequality in the Bali region during the 2016-2020 period using four independent variables, namely economic growth, government expenditure, employment, workers with upper secondary education, and investment. With this data then analyzed based on the plate data regression method procedure. The results obtained from the panel data regression analysis are that the fixed effect model (FEM) is the most appropriate approach to explain the effect of the dependent variable on the independent variable in this study. Based on the effect validity test or t test, the variables that have a significant effect on income inequality in Bali Province in 2016-2020 are known to be economic growth, government expenditure and employment with coefficients related to negative, positive and positive trends.